Navigating Agents In Uncertain Environments Using Particle Swarm Optimisation - -, Adham Atyabi (2008)
This study introduces enhanced versions of Particle Swarm Optimization (PSO) to handle the real-world navigation problems. These modified versions of PSO are known as Particle Swarm Optimization with Area Extension (AEPSO) and Cooperative AEPSO (CAEPSO).